2021
DOI: 10.1371/journal.pone.0254517
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting guardians’ decision making on clinic-based purchase of children’s spectacles in Nigeria

Abstract: Background This study aims to understand the key factors influencing guardians’ decisions when purchasing spectacles for their children in semi-urban and urban areas of Cross River State, Nigeria, where a spectacle cross-subsidisation scheme will be implemented. Methods This cross-sectional study was conducted among all consecutive guardians visiting the Calabar (urban), Ugep, Ikom and Ogoja (semi-urban) public eye clinics in Cross River State, southern Nigeria, from August 1 to October 31 2019, and whose ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Ajaiyeoba et al's population-based study in Nigeria 17 found that refractive error was almost twice as common in girls as in boys. Our earlier study 4 found that parents prioritised frame design, material and quality when purchasing spectacles for their children. Taken together, these findings indicate that planning for spectacle inventory should consider the gender balance of refractive error and what parents consider attractive and appropriate for daughters as well as sons.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ajaiyeoba et al's population-based study in Nigeria 17 found that refractive error was almost twice as common in girls as in boys. Our earlier study 4 found that parents prioritised frame design, material and quality when purchasing spectacles for their children. Taken together, these findings indicate that planning for spectacle inventory should consider the gender balance of refractive error and what parents consider attractive and appropriate for daughters as well as sons.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous work, which looked at user behavioural profiles, found that spectacle frame design, material and quality are key factors influencing guardians when purchasing spectacles for their children. 4 We further determined a need to correct misperceptions among parents regarding their children's vision and ocular conditions to increase the demand for child eye care services. 5 This article focuses on understanding the clinics' current patients to inform the development of a sustainable spectacles cross-subsidisation scheme.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…On the other hand, two studies conducted in Nigeria showed other factors influencing the decision to buy eyeglasses for children. In one study, frame design, material and quality were the deciding factors [ 40 ]; in the second study, parents were aware of the need for eyeglasses for their children but were reluctant to have eyeglasses corrected because they perceived wearing eyeglasses as a stigma [ 17 ]. In a review by Burnett and colleagues, interventions and methods were identified to improve eye-care services for school children in low- and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…To fill this knowledge gap, we conducted a study to explore reasons for referral nonadherence. This study is part of a larger research project, described elsewhere [ 20 ], to help the Nigerian government improve and scale up its child eye care programme.…”
Section: Introductionmentioning
confidence: 99%